2010
DOI: 10.1373/clinchem.2010.147124
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Physicochemical State of C-Reactive Protein in Different Preparations Including 2 Certified Reference Materials

Abstract: BACKGROUND Standardization of clinical measurements of C-reactive protein (CRP) is based on the availability of reference materials. The serum protein reference material ERM-DA470 was used as a calibrant for various commercially available immunoassays but has now been exhausted. The recently released ERM-DA470k/IFCC was intended to fully replace ERM-DA470. However, the new material was not suited for the certification of CRP because of a bias introduced by the lyophilization process that caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It was later found that lyophilization can induce changes in the oligomeric structure of CRP (16 ). Therefore, CRP was not certified in ERM-DA470/IFCC, and a separate liquid frozen material was produced (ERM-DA472/IFCC) and found to be suitable.…”
Section: Fig 3 Results Of the Characterization Measurements For Albmentioning
confidence: 99%
“…It was later found that lyophilization can induce changes in the oligomeric structure of CRP (16 ). Therefore, CRP was not certified in ERM-DA470/IFCC, and a separate liquid frozen material was produced (ERM-DA472/IFCC) and found to be suitable.…”
Section: Fig 3 Results Of the Characterization Measurements For Albmentioning
confidence: 99%
“…8 However, the recovery of lactate dehydrogenase, glucose 6-phosphate dehydrogenase and C-reactive protein has been shown to be lower and in the region of 80%. 9,10 Differences in the recovery between target molecules may be attributable to differences in the handling of samples before freeze-drying, in particular temperature which promotes protein denaturation and irreversible adhesions. It is, therefore, imperative to ensure that sample processing is carried out in the mildest possible conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies confirmed the enhanced interactions of mCRP with modified lipoproteins [61] and complement [62][63][64][65][66][67] and further revealed the important contributions of mCRP in promoting non-inflammatory clearance of apoptotic or necrotic cells by controlling complement activation on the cell surface through balanced recruitment of C1q, Factor H and C4bp [64][65][66]. Because inappropriate handling of CRP, including lyophilization [68], storage in the absence of calcium [69] and immobilization onto microtiter wells [60,70], leads to the disruption of the pentameric structure, the reported properties of CRP suffering these technical pitfalls should be re-evaluated with Factor H interaction as a prominent example [60,64,71].…”
Section: The Bioactivities Of Crp Are Dependent On Conformational Statesmentioning
confidence: 88%